Growth and Yield Characteristics of Chilli as Affected by Nitrogen in Presence and Absence of Phosphorus and Potassium: Nitrogen for Growth and Yield of Chilli - Baloch, Parwaiz Ahmed; Abro, Bashir Ahmed; Solangi, Abdul Hameed; Siddiqui, Aqeel Ahmed (Biological Sciences - PJSIR, 2013)